Characterization of the coral communities and reefs ot two previously underscribed locations in the upwelling region of Gulf of Papagayo Costa Rica - Jiménez, Carlos (2010)
In the seasonal upwelling region of Gulf of Papagayo (Northern Pacific coast of Costa Rica), we evaluated and described two previously poorly known coral habitats, Punta Cacique and Bahía Guacamaya. Both localities differed in the extent of the frame-building coral communities and their composition. While Bahía Guacamaya and Punta Cacique had a similar number of coral species (16), live coral cover percent was higher in the coral reefs (ca. 50% vs. 90%) and coral communities (ca. 40% vs. 50%) of the latter. At both localities, branching species (Pocillopora spp.) contributed more as a group to the live coral cover than massive and encrusting corals. Bahía Guacamaya has the largest colonies found so far of two coral species (Pocillopora eydouxi and Pocillopora meandrina) with a limited distribution in Costa Rica. Using long-term records of environmental data, we characterized the seasonality of the upwelling and the dry and rainy seasons that partially explained the low suspension sediment loads and fresh water discharge into Papagayo’s coral habitats. The results of our study are important due to the rapid development of the coastal zone of Papagayo and because only a fraction of the littoral has been systematically surveyed. Therefore, we call for more studies that aim to produce baseline data of coral habitats in the area.